Réponses

2014-01-05T18:02:53+01:00
A=(3x-5)²+(3x-5)(x+7) et B=(2x-5)(4x-1)-(x+2)(2x-5)
Developper et réduire
A=(3x-5)²+(3x-5)(x+7)
=9x²-30x+25+3x²+21x-5x-35
=12x²-14x-10

Factoriser A
A=(3x-5)²+(3x-5)(x+7)
=(3x-5)(3x-5+x+7)
=(3x-5)(2x+2)
=2(3x-5)(x+1)

Calculer A pour x = 2 avec 12x²-14x-10
12*2²-14*2-10
=12*4-28-10
=48-28-10
=10

Developper et réduire
B=(2x-5)(4x-1)-(x+2)(2x-5)
=8x²-2x-20x+5-(2x²-5x+4x-10)
=8x²-2x-20x+5-2x²+5x-4x+10
=6x²-21x+15

Factoriser 
B=(2x-5)(4x-1)-(x+2)(2x-5)
=(2x-5)(4x-1-x-2)
=(2x-5)(3x-3)
=3(2x-5)(x-1)